Ruínas de mundos perdidos: a estética residual de Brennand - Ana Luiza Andrade (Estudos de Literatura Brasileira Contemporânea)
This study tries to understand modern ruins through a Benjaminian reading. Besides analyzing Brennand’s heads as remainders of worlds which were lost in catastrophes, it relates Brennand’s sculptures to ruins in the works of some writers and poets such as Osman Lins, Antonio José Ponte, João Cabral de Melo Neto and Jorge Luis Borges.